HAK KONSTITUSIONAL BURUH PEREMPUAN DALAM BINGKAI NEGARA HUKUM KESEJAHTERAAN DI INDONESIA - Triana Sofiani (Muwazah, 2014)
Abstract : This study just want to expose on the constitutional rights of women workers in Indonesia within the legal framework of the welfare state. Indonesia as a state welfare law, of course, the duty to enforce the welfare of all citizens, both men and women without discrimination, including the constitutional rights of women workers. The state is obliged regulate wages, provide protection, social security and guarantee of other rights, fairly and without discrimination in accordance constitutional rights of women workers as the provisions contained in the Constitution of the Republic of Indonesia 1945. Abstrak : Penelitian ini hanya ingin mengekspos tentang hak-hak konstitusional pekerja perempuan di Indonesia dalam kerangka hukum negara kesejahteraan. Indonesia sebagai hukum negara kesejahteraan, tentu saja, kewajiban untuk menegakkan kesejahteraan semua warga negara, baik pria maupun wanita tanpa diskriminasi, termasuk hak-hak konstitusional pekerja perempuan. Negara berkewajiban mengatur upah, memberikan perlindungan, jaminan sosial dan jaminan hak-hak lain, adil dan tanpa diskriminasi dalam hak-hak konstitusional sesuai pekerja perempuan sebagai ketentuan yang tercantum dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945.